(untitled) (Journal of Nepal Geological Society, 2017)
Since the collision between the Indian and Asian plates, several peripheral foreland basin were formed, and started to accumulate the sediments from the hinterland Himalayan orogeny. The sediments deposited at the northern tip of the Greater India have been uplifted, exhumed after the activation of several south propagating thrusts and finally transported to the foreland basin by southward flowing fluvial system. We present petrography and detrital zircon dating for the interpretation of possible provenance of the Neogene Siwalik foreland basin sediments in far western Nepal. The QFL ternary plot for provenance analysis show a ’recycled orogeny’ field for the studied sandstone samples, indicating Tethys Himalaya, Higher Himalaya and Lesser Himalaya as the source of the foreland basin sediments. The detrital zircon U-Pb ages of the studied samples have shown that during the time of deposition there was dominant numbers of detritus supplied from the Tethys and upper Lesser Himalaya. Subsequently the amount of the Higher and Lower Lesser Himalaya increased during the time of deposition of the Middle Siwalik.